Smart Differentiation System using Self-Adaptive Ensemble-based Differential Evolution (SAEDE) as a Learning Aid for Learning Differentiation - Munirah Mazlan; Wang Shir Li; Haldi Budiman; Suzani Mohamad Samuri (Pejabat Karang Mengarang UPSI, 2021)
Future workforce skills are dominated by a good understanding of technology and engineering, and problem-solving skills. Therefore, the importance of science, technology, engineering, mathematics (STEM) education is globally recognized. Among the STEM-related subjects, mathematics is known as a challenging subject. Mathematics learning during pandemic Covid 19 becomes more challenging when students are encouraged to self-learn at home. An appropriate combination of pedagogy and technology such as artificial intelligence (AI) will benefit mathematical learning.  Therefore, this study is to investigate the effectiveness of an AI-based learning aid for a mathematics topic, which is differentiation. An artificial intelligence-based learning aid known as the "Smart Differentiation System" or known as SDS in short,  is developed to allow students to cross-check differentiation solutions in solving differential equations. An AI technique called Self-Adaptive Ensemble Based Differential Evolution (SAEDE) is integrated into the development of the Smart Differentiation System. Smart Differentiation System is developed based on the Agile model. A multiple-choice questionnaire is used to collect data from the target group of respondents regarding their problems in learning mathematics and feedback about the Smart Differentiation System. Based on the results, 86.7% of the respondents agreed that the use of Smart Differentiation System as a learning aid in the classroom is more fun and exciting and 80% agreed that Smart Differentiation System is acceptable and can be used by secondary school students in learning mathematics. In conclusion, the learning aid has determined the effectiveness of the AI-based learning aid especially in helping students to perform self-learning in mathematics.